Impact of social Media and Google on stock Markets During a Pandemic: The Case of an Airline - A. N. Nepp; Z. F. Dzhuraeva (Финансы: теория и практика, 2023)
The outbreak of the pandemic has dealt a tangible blow to the global economy, in particular by causing the collapse of stock markets. Most countries have taken measures to contain the coronavirus related to the restriction of human mobility. One of the main victims of such actions were airlines. In order to examine the direct and indirect effects of the pandemic, we investigated the long- and short-term effects on airline stock price volatility of the spread of coronavirus, social media attention to it, the vaccines against coronavirus and restrictive measures in relation to the pandemic. The ARDL model with MG and PMG estimates was applied after the preliminary stability tests for airlines in developed and developing countries. We analyzed the period of the greatest anti-COVID restrictions from 23 March 2020 to 23 March 2021. We reached the following conclusions. Firstly, the increase in the number of cases and deaths from COVID-19 was accompanied by a short-term increase in the volatility of airline stock prices. Secondly, Twitter’s increased focus on COVID-19-related restrictive measures and vaccines against it was accompanied by a short-term increase in airline stock price volatility. Thirdly, the increasing attention at Google on airline restrictions has been accompanied by the long-term effects of rising stock volatility. Our results demonstrate that with the spread of the Internet and social media, the impact of the pandemic on stock markets occurs not only through direct effects on the determinants of Solow’s economic growth model, but also through indirect effects of social media and the Internet on investor behavior through the formation of fear and hysteria in them.